PERAN EDUKASI KEAGAMAAN DALAM MEMBENTUK KEPRIBADIAN WANITA PENJAJA SEKS DI INDONESIA - Alfiatu Solikah; Widyasmoro, Hari; Jamroji, Bagus; Ibnu Soleh, M.; Khodijah, Siti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This research aims to describe and analyze the role of Islamic religious education conducted by religious counselors in shaping the personalities of female sex workers in Kediri Regency. The classic problem of prostitution persists without a solution. Islamic religious counselors in Kediri Regency attempt to provide a solution through religious education for female sex workers (FSWs). This study is based on the social control theory, employing a qualitative phenomenological approach. Data collection methods include observation and interviews, with phenomenological data analysis. The research involves Islamic religious counselors and female sex workers in Kediri Regency. The findings of this study conclude that: First, Islamic religious counselors conduct religious education for female sex workers by establishing Islamic boarding schools in the midst of red-light districts; Second, the implementation of religious education utilizes methods, materials, and strategies tailored to the needs of FSWs; Third, religious education transforms the personalities of female sex workers, leading them back to the right path, fostering a more religious lifestyle, and transitioning to different professions.